2021
DOI: 10.2196/20779
|View full text |Cite
|
Sign up to set email alerts
|

Video Consultation as an Adequate Alternative to Face-to-Face Consultation in Continuous Positive Airway Pressure Use for Newly Diagnosed Patients With Obstructive Sleep Apnea: Randomized Controlled Trial

Abstract: Background The effectiveness of continuous positive airway pressure (CPAP) is dependent on the degree of use, so adherence is essential. Cognitive components (eg, self-efficacy) and support during treatment have been found to be important in CPAP use. Video consultation may be useful to support patients during treatment. So far, video consultation has rarely been evaluated in thorough controlled research, with only a limited number of outcomes assessed. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Studies analyzing different telemedicine strategies for CPAP follow-up have found that CPAP compliance was equivalent to that with usual care (18,(25)(26)(27)(28). Only a few studies were successful in increasing CPAP compliance up to 30 min/night through phone coaching implementation (26 min/night) (29), or other methods .Nevertheless, a recent CPAP telemonitoring meta-analysis (22) did not find differences in CPAP compliance with telemonitored and standard CPAP follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Studies analyzing different telemedicine strategies for CPAP follow-up have found that CPAP compliance was equivalent to that with usual care (18,(25)(26)(27)(28). Only a few studies were successful in increasing CPAP compliance up to 30 min/night through phone coaching implementation (26 min/night) (29), or other methods .Nevertheless, a recent CPAP telemonitoring meta-analysis (22) did not find differences in CPAP compliance with telemonitored and standard CPAP follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[104] There is increasing evidence that this approach is at least as effective as face-to-face reviews and may enable more timely management. In terms of service delivery, telemonitoring has been deemed feasible in a range of healthcare systems, [105][106][107][108] facilitating access to CPAP initiation, [105] promoting timely titration of therapy, [106,109,110] and troubleshooting of technical problems. [106,111] A meta-analysis (n=11 RCTs; 1440 patients) concluded that overall telemedicine improved adherence compared to centre-based care.…”
Section: Monitoring To Support Remote Consulting In Obstructive Sleep...mentioning
confidence: 99%
“…[108,110,113,114] Telemonitoring and video consultations (see Figure 4) are generally well accepted by patients using CPAP therapy. [103,[107][108][109][110][114][115][116] The time savings reduce the impact on work productivity and the reduced travel and fuel consumption costs are valued as environmentally friendly. [59] Remote monitoring to reduce exacerbations of COPD Key objectives of COPD telemonitoring are to reduce exacerbations (especially severe exacerbations resulting in distressing and costly admissions) and improve quality of life.…”
Section: Monitoring To Support Remote Consulting In Obstructive Sleep...mentioning
confidence: 99%
“…Of these, 63 studies were retrieved for full-text review and assessment for eligibility. 51 studies did not meet the inclusion criteria and a total of 12 studies [22][23][24][25][26][27][28][29][30][31][32][33] were included in the review as outlined in the PRISMA flow diagram (figure 1). The commonest reason for exclusion was "wrong intervention" (n=16).…”
Section: Overview Of Eligible Studiesmentioning
confidence: 99%
“…Adherence to CPAP therapy CPAP therapy usage, assessed objectively, was reported by all included studies (n=12). The average CPAP usage at follow-up assessment ranged from 3.5 to 5.6 h per night with virtual consultations and 2.1 to Other bias TAYLOR et al [22] STEPNOWSKY et al [23] ISETTA et al [24] FRASNELLI et al [26] FIELDS et al [25] TURINO et al [27] LUGO et al [28] NILIUS et al [29] PÉPIN et al [30] TAMISIER et al [31] FIETZE et al [33] KOOIJ et al [32] Low risk of bias…”
Section: Secondary Outcomesmentioning
confidence: 99%